Orgasm. On the flux and flow of a term through times and spaces - Christina Goestl (Glad!)
My video essay tells the story of the construction of the term “orgasm” throughout Western history. The ancient term orgasm had multiple meanings ― swelling and being excited, intense or violent excitement. Texts before the nineteenth century describe excitement and mention ejaculation, but do not use the term “orgasm”. In the nineteenth century the term was increasingly used with a sexual connotation. It was not until the twentieth century that “orgasm” became an exclusively sexual term. In the context of this linguistic development, “orgasm” became a factor that was assigned a productive function in society. This development has also always been criticized as a normative physiological construct whose fixation on genitalia and function narrows our understanding of the pleasures and joys of sexual bodies. Tracing the term through time, the question arises how pleasure was talked about before the term “orgasm” developed its current meaning and relevance. What perceptions, ideas and descriptions about lust can be found in times when the term was still absent? Are there entirely different notions of pleasure yet to be discovered? And if so, what do they share with contemporary feminist and queer concepts, and what inspirations do they offer?